2021
DOI: 10.1108/ijem-02-2020-0114
|View full text |Cite
|
Sign up to set email alerts
|

Teacher job satisfaction in Taiwan: making the connections with teacher attitudes, teacher self-efficacy and student achievement

Abstract: PurposeThis paper aims to describe the findings of a study investigating the relationships between teacher attitudes to teaching mathematics, teacher self-efficacy, student achievement and teacher job satisfaction in Taiwan.Design/methodology/approachData were collected from 110 fifth grade primary school teachers and their students (n = 2,334) between 10 and 10 years old. A teacher questionnaire and a criterion-reference test in mathematics were distributed during the academic year 2016–2017. The data were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…Teacher self-efficacy strongly links to job satisfaction (Caprara et al, 2003), impacting it by fostering accomplishment, reducing stress, improving student outcomes, and enhancing relationships with students and colleagues. A strong sense of teacher self-efficacy ensures effective classroom management (Abu-Tineh et al, 2011), leading to positive outcomes for students (Tsai and Antoniou, 2021). These outcomes contribute to a supportive work environment, fostering pride and accomplishment, ultimately influencing teacher satisfaction.…”
Section: Underpinning Theorymentioning
confidence: 99%
“…Teacher self-efficacy strongly links to job satisfaction (Caprara et al, 2003), impacting it by fostering accomplishment, reducing stress, improving student outcomes, and enhancing relationships with students and colleagues. A strong sense of teacher self-efficacy ensures effective classroom management (Abu-Tineh et al, 2011), leading to positive outcomes for students (Tsai and Antoniou, 2021). These outcomes contribute to a supportive work environment, fostering pride and accomplishment, ultimately influencing teacher satisfaction.…”
Section: Underpinning Theorymentioning
confidence: 99%
“…It can also make the decisions made by managers really implemented in each teaching link. Therefore, the participation of teachers in administrative management is a win-win for both schools and teachers, and can minimize the sense of oppression generated by teachers in the management system, which is also helpful to improve teachers' job satisfaction [10][11].…”
Section: Let Teachers Participate In Administrationmentioning
confidence: 99%
“…Job satisfaction is a status of emotion aroused during the interaction with the people and environment in the workplace [13,21]. Teachers evaluate job satisfaction by comparing desired job environment with incumbent status [15].…”
Section: Teacher Job Satisfactionmentioning
confidence: 99%
“…Increasing studies have reported the relationships between mathematics teacher job satisfaction and stress in teaching practice [9,10]. Because job satisfaction and stress are linked to teachers' commitment, engagement, emotional exhaustion, student support, self-efficacy, and burnout, teacher job satisfaction and stress influence their instructional practice [11][12][13][14][15]. Considering dialogic instruction requires teachers' intensive effort and commitment [4], we could assume that mathematics teachers with high job satisfaction and low level of stress are more likely to implement dialogic instruction.…”
Section: Introductionmentioning
confidence: 99%